How diversification affects innovation by a Korean mobile content firm. (4th September 2012) - Jung, Hyejae; Kim, Eungdo; Kim, Seunghyun; Hwang, Junseok
The purpose of this paper is to analyse the factors affecting innovation in a mobile content firm in Korea, with a focus on diversification. We analysed the effect of firm strategy (diversification), capabilities (R&D activity, R&D personnel, marketing capabilities) and characteristics (firm size and age) on innovation. We conducted a detailed analysis on how the extent and direction of diversification influences innovation. For the analysis, we used a negative binomial model with five year panel data adapted from the Data Analysis, Retrieval and Transfer System (DART) database for 41 firms listed in the Korea Mobile Yearbook 2009–2010. The analysis results indicated that the extent of diversification has a negative correlation with innovation, while horizontal diversification has a positive correlation with innovation. Through this study, we draw the policy significance of diversification in relation to the effective fostering and capacity intensification of innovation in the Korean mobile content industry.